2011
DOI: 10.1111/j.1464-5491.2011.03240.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of pitavastatin and atorvastatin on lipoprotein subclasses in patients with Type 2 diabetes mellitus

Abstract: The impact on lipoprotein subclass profiles was different between pitavastatin and atorvastatin. It may be beneficial to determine lipoprotein subclass profile and select the appropriate statin for each profile in patients with diabetes with an additional cardiovascular risk such as low HDL cholesterol or hypertriglyceridaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…39 In a post hoc analysis of the Treating to New Targets study, 40 HDL-C levels during statin treatment were inversely related to the risk of cardiovascular events, even among patients with LDL-C levels , 70 mg/dL. Giving a major increase of HDL-C 35 and of apolipoprotein A1, 33 pitavastatin has a further positive effect on reducing coronary atherosclerosis. This was confirmed by Maruyama et al that observed that, despite giving a similar reduction of LDL-C, pitavastatin resulted superior to atorvastatin in reducing major adverse cardiac events, due to their differing HDL-C raising ability.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…39 In a post hoc analysis of the Treating to New Targets study, 40 HDL-C levels during statin treatment were inversely related to the risk of cardiovascular events, even among patients with LDL-C levels , 70 mg/dL. Giving a major increase of HDL-C 35 and of apolipoprotein A1, 33 pitavastatin has a further positive effect on reducing coronary atherosclerosis. This was confirmed by Maruyama et al that observed that, despite giving a similar reduction of LDL-C, pitavastatin resulted superior to atorvastatin in reducing major adverse cardiac events, due to their differing HDL-C raising ability.…”
Section: Discussionmentioning
confidence: 96%
“…[24][25][26][27] Compared to other previously commercialized statins, pitavastatin proved to be as effective as atorvastatin in terms of the proportions of patients achieving the LDL-C goal, reductions in LDL-C, TC, and Tg, [26][27][28][29][30][31][32][33][34] but to be inferior to rosuvastatin in lowering LDL-C, and hs-CRP in patients with type 2 diabetes mellitus, 38 placing between atorvastatin and rosuvastatin in terms of effectiveness (Table 3). Moreover, compared to other statins, pitavastatin treatment was also associated with a significant greater increase in HDL-C levels ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of stable CAD patients with chronic total occlusion with type 2 diabetes mellitus, Shen et al found LDL-C and non HDL-C as predictors for poor collateral development [37]. We did not include diabetic patients in our study group since in DM patients HDL-C is low and LDL-C and TG-rich lipoproteins are high [38,39]. There are no studies investigating the relationship between non-HDL-C and CCC.…”
Section: Discussionmentioning
confidence: 99%
“…97 Newer statins such as pitavastatin have been studied in both type 2 diabetes and metabolic syndrome, with excellent efficacy. 77,142 In addition, the efficacy and safety of pitavastatin have been studied in elderly patients in Phase III studies. 69,143 As a result of its structure and metabolism, pitavastatin could possibly be better tolerated than other statins in these populations who are frequently on polypharmacy drug regiments.…”
Section: Future Of Dyslipidemia Treatment In Special Populationsmentioning
confidence: 99%